2020
DOI: 10.1016/j.jaac.2019.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories in Symptoms of Autism and Cognitive Ability in Autism From Childhood to Adult Life: Findings From a Longitudinal Epidemiological Cohort

Abstract: Objective: For the first time, we use a longitudinal population-based autism cohort to chart the trajectories of cognition and autism symptoms from childhood to early adulthood and identify features that predict the level of function and change with development. Method: Latent growth curve models were fitted to data from the Special Needs and Autism Project cohort at three time points: 12, 16, and 23 years. Outcome measures were IQ and parent-reported Social Responsiveness Scale autism symptoms. Of the 158 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
3
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 43 publications
6
78
3
6
Order By: Relevance
“…et al (2014) found that autistic adults without intellectual disability were less likely to live independently or to have obtained employment compared to non-autistic adults with intellectual disability. Social factors, such as attendance in mainstream schooling may also exert an influence on outcome, potentially more so than IQ (Simonoff et al 2019). These studies suggest that behavioural, cognitive, or social factors not necessarily associated with IQ may affect outcome.…”
Section: Discussionmentioning
confidence: 81%
“…et al (2014) found that autistic adults without intellectual disability were less likely to live independently or to have obtained employment compared to non-autistic adults with intellectual disability. Social factors, such as attendance in mainstream schooling may also exert an influence on outcome, potentially more so than IQ (Simonoff et al 2019). These studies suggest that behavioural, cognitive, or social factors not necessarily associated with IQ may affect outcome.…”
Section: Discussionmentioning
confidence: 81%
“…First, we compared participants with and without ASD across the variables described above. For continuous variables, we compared means with Welch’s two-sided unequal variances t -test, and for categorical variables we compared frequency counts with Pearson’s χ 2 . Within each of these sets, we used the Benjamini-Hochberg procedure to control the false discovery rate.…”
Section: Methodsmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) and schizophrenia (SCZ) are separate diagnostic entities that in some respects show clear divergence. ASD, typically diagnosed in childhood, is characterized by the combined presence of social communication deficits and restricted or repetitive behaviors 1 and tends either to have a stable course or to show clinical improvement with time 2 . SCZ, typically diagnosed in late adolescence or early adulthood 3 , is characterized by psychosis, which reflects a loss of contact with reality, and manifests as delusional beliefs or hallucinatory experiences 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 100 autistic adolescents and 57 nonautistic adolescents who had an IQ ≥ 50, were assessed as part of the Special Needs and Autism Project (SNAP) cohort (see Baird et al, 2006 for details). Participants were recruited at 12 years and followed up in adolescence and young adulthood (Simonoff et al, 2020). Here we report upon data from adolescence (mean age 16 years) (see Charman et al, 2011 for details).…”
Section: Methodsmentioning
confidence: 99%